Anomalous aging of EPDM and FEPM under combined thermo-oxidative and hydrolytic conditions. (December 2017) - Redline, Erica M.; Celina, Mathias C.; Harris, Charles E.; Giron, Nicholas H.; Sugama, Toshifumi; Pyatina, Tatiana
Abstract: Previous observation of EPDM and FEPM materials aged in thermo-oxidative and thermo-oxidative plus hydrolytic environments revealed an unusual trend: the degradation and disintegration of these polymers in the former case but the ability to maintain mechanical performance and shape in the latter [1]. No abnormalities were observed in the chemical (oxidation rates, FTIR spectra, solvent uptake, gel content, and weight loss vs. temperature) or physical (modulus profile) measurements that could explain these empirically observed aging differences. A second controlled aging test was conducted to verify this trend using only EPDM. Once again it was shown that thermo-oxidative conditions appear to cause more degradative damage (enhanced embrittlement) than observed for the combined thermo-oxidative plus hydrolytic environments. From these data we conclude that water may favorably interfere with normal thermo-oxidative degradation processes. This interference may occur via some combination of chemical and physical property changes in the presence of steam such as: oxidation rate and O2 permeability changes, additional sensitivity to hydrolytic damage, and/or mechanistic changes in relation to pH and hydroperoxide formation.